Pengaruh Penerapan Sistem e-Filling Dengan Pemahaman Internet Terhadap Kepatuhan Wajib Pajak Sebagai Variabel Moderasi Di KPP Pratama Karawang Utara - Trias Arimurti; Yanti Yanti; Ulfa Sasqia (Jurnal Widya Akuntansi dan Keuangan, 2021)
E-filling is a service for filling and submitting Taxpayer Tax Returns), which is carried out electronically through a real-time online system to prepare and submit SPT. This research will specifically examine how the implementation of the e-filling system on taxpayer compliance, then find out how internet understanding can moderate the relationship between the e-filling system and taxpayer compliance and how much influence the application of the e-filling system and internet understanding has on taxpayer compliance. This research is a type of causality that uses a quantitative approach. The population of this research is Individual Taxpayer ASN Karawang District which works in the Government Institution of North Karawang. The sample used in this study was 100 respondents. The data is processed using multivariate regression technique with moderation testing. The results of data analysis, i.e., The application of the e-filling system filling on Taxpayer Compliance, does not have a statistically significant effect, while is moderated by an internet understanding of Taxpayers, is proven to be significant concerning Taxpayer Compliance. The contribution of applying the e-filling system and internet understanding to taxpayer compliance with taxpayers at KPP Pratama Karawang Utara is only 3.9 percent.